Anos de chumbo : rock e repressão durante o AI-5 - Saggiorato, Alexandre (2008)
This work presents a study about the Rock made in Brazil during the military dictatorship, precisely at the time with greater repression and censorship by the institutional act number (Ato Institucional Nº5, AI-5), under not only the perspective of the transgressed behavior of the military dictatorship s moral censorship, but also by the attempt of artistic engagement done by the left-wing part. However, the work and the behavior of some Rock groups of that period will be explored, among these we point out: Novos Baianos, Casa das Máquinas and O Terço, being through their social construction, our point of investigation upon the effects in the repression on the Brazilian Rock of 1970, understanding the way these artists acted at that time.